The Influence of Leadership, Employee Empowerment, and Work Motivation on the Performance of Rubber Tappers at PTPN III Tanah Raja Estate - Arga Malona; Yusniar Lubis; Syaifudin Lubis (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2026)
This study aims to examine the effects of leadership and employee empowerment on the performance of rubber tappers, with work motivation serving as an intervening variable at PTPN III Tanah Raja Estate, North Sumatra. A quantitative research approach was employed using a survey method involving 127 rubber tappers selected through total sampling. Primary data were collected using structured questionnaires and analyzed using path analysis. The findings reveal that leadership and employee empowerment have positive and significant effects on employee performance. In addition, work motivation significantly improves employee performance and mediates the relationship between leadership, employee empowerment, and performance. These results indicate that effective leadership practices and employee empowerment contribute to higher levels of work motivation, which subsequently enhances the performance of rubber tappers. Therefore, plantation management should strengthen leadership quality and implement employee empowerment strategies to improve workforce productivity and organizational performance. The study provides empirical evidence that human resource development plays a crucial role in achieving sustainable performance in the plantation sector..